Vagus nerve stimulation suppresses corticotropin-releasing factor-induced adrenocorticotropic hormone release in rats. Issue 9 (9th June 2021) - Chen, Xiao; Liang, Huaibin; Hu, Kejia; Sun, Qingfang; Sun, Bomin; Bian, Liuguan; Sun, Yuhao
Abstract : Adrenocorticotropic hormone (ACTH)-dependent Cushing's syndrome is characterized by hypothalamus-pituitary-adrenal axis dysfunction. As the neuroendocrinological axis has been shown to react under the regulation of the central nerve system through the corticotropin-releasing factor (CRF) releasing from the hypothalamic paraventricular nucleus. Whether one of the neuromodulation therapies, vagus nerve stimulation, is able to treat this neuroendocrinological disorder remains unknown. In this study, we explored the effects of vagus nerve stimulation (VNS) on CRF-induced serum ACTH level change in normal rats. After the vagus nerve electrode placement, the ACTH and corticosterone levels were measured multiple times before and after the administration of CRF (2 μg/kg) in switched-ON and -OFF groups, respectively, compared to the control group. Our results showed that 2 h continuous stimulation on the vagus nerve inhibited CRF-induced ACTH release up to 1 h compared with the control group, while the corticosterone level was not influenced. The vagus nerve might be a potential therapeutic target in the treatment of ACTH-dependent Cushing's syndrome disorders involving hypothalamus-pituitary-adrenal axis dysfunction.